Pengaruh Perbandingan Mocaf (Modified Cassava Flour) Dan Tepung Kacang Tanah (Arachis hypogaea L.) Terhadap Karakteristik Fisikokimia Dan Sensoris Flakes Gluten Free - Priyanka Saraswati, Putu; Sri Wiadnyani, Anak Agung Istri; Ari Yusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p07, 2023)
Flakes that are sold in Indonesia’s market are mostly made of wheat or cereal. Most of the nutritional content in flakes is carbohydrates, but people need complete nutrition for breakfast. Mocaf and peanut flour can be used to improve the nutritional value of flakes. This study aims to determine the physico-chemical and sensory properties of gluten free flakes made of mocaf and groundnut flour and also to obtain the right ratio of mocaf and peanut flour to produce flakes with the best physicochemical and sensory properties. The design used in this study was a completely randomized design (CRD) with a ratio of the amount of mocaf and groundnut flour (100%:0%, 90%:10%, 80%:20%, 70%:30%, and 60%:40%). All treatments were repeated three times to obtain 15 experimental units. The data obtained were analyzed by means of variance and if the treatment had a significant effect, continued with the Duncan Multiple Range Test. The results showed that the ratio of mocaf and groundnut flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, crunch time, scoring test on color, aroma, taste, hedonic test on color, aroma, texture, taste, and overall acceptance. A comparison of 70% mocaf and 30% groundnut flour produced flakes with the best physico-chemical and sensory properties with the criteria of water content 3.87%, ash content 1.65%, protein content 9.18%, fat content 24.00%, carbohydrate content 61.45%, crude fiber content 2.76%, crunch time 6.50 minutes, as well as sensory properties of light brown color and liked, peanuts flavored and liked, crunchy texture and liked, taste very liked and overall acceptance liked.